From order to chaos : Essays : Critical, chaotic and otherwise - Kadanoff, Leo P. (Singapore World Scientific, 1993)
This book is a compilation of the review papers, expositions and some of the technical works of Leo Kadanoff, a theoretical physicist. The objective is to put together a group of not-too-technical writing in which he discusses some issues in condensed matter physics, hydrodynamics, applied mathematics and national policy.
Includes references and index.
Keywords: Cơ bản